PREPARATION, CHARACTERIZATION, ACTIVITY, DEACTIVATION, AND REGENERATION TESTS OF CoO-MoO/ZnO AND CoO-MoO/ZnO-ACTIVATED ZEOLITE CATALYSTS FOR THE HYDROGEN PRODUCTION FROM FUSEL OIL - Wega Trisunaryanti; Ignatius Emmanuel (Universitas Gadjah Mada, 2009)
Preparation, characterization, activation, deactivation, and regeneration tests of CoO-MoO/ZnO and CoO-MoO/ZnO-Activated Zeolite (AZ) catalysts for the hydrogen production using steam reforming of alcohols in fusel oil have been conducted. Both catalysts were prepared by impregnation of Co and Mo onto ZnO or ZnO-AZ powder then followed by calcination at 400 °C for 5 h under N2 stream. The BET method and pyridine adsorption were used for catalysts characterization. The study of activation, deactivation, and regeneration of catalysts were conducted by using steam reforming method in the semi flow reactor. The reaction condition were: weight ratio of catalysts/feed = 0.1, temperature: 450°C, duration: 45 min. The gas product was trapped in a 250 mL vacuum pyrex bottle filled with 50 mL of 4 M NaOH solution and analyzed by GC with TCD system to determine H2 existance and HCl titration to determine CO2 produced during the process that was dissolved in NaOH solution. The results showed that CoO-MoO/ZnO-AZ catalyst produced higher gas conversion than CoO-MoO/ZnO catalyst. However, it had short catalyst lifetime due to its high amount of coke deposited during the process. The regeneration test could enhance the catalyst activity. The gas product consisted of H2 (14.70%) and CO2 (24.41%).